Chromosomal rearrangements in the 11p15 imprinted region: 17 new 11p15.5 duplications with associated phenotypes and putative functional consequences. Issue 3 (9th December 2017) - Heide, Solveig; Chantot-Bastaraud, Sandra; Keren, Boris; Harbison, Madeleine D; Azzi, Salah; Rossignol, Sylvie; Michot, Caroline; Lackmy-Port Lys, Marilyn; Demeer, Bénédicte; Heinrichs, Claudine; Newfield, Ron S; Sarda, Pierre; et al.
Abstract : Background: The 11p15 region contains two clusters of imprinted genes. Opposite genetic and epigenetic anomalies of this region result in two distinct growth disturbance syndromes: Beckwith-Wiedemann (BWS) and Silver-Russell syndromes (SRS). Cytogenetic rearrangements within this region represent less than 3% of SRS and BWS cases. Among these, 11p15 duplications were infrequently reported and interpretation of their pathogenic effects is complex. Objectives: To report cytogenetic and methylation analyses in a cohort of patients with SRS/BWS carrying 11p15 duplications and establish genotype/phenotype correlations. Methods: From a cohort of patients with SRS/BWS with an abnormal methylation profile (using ASMM-RTQ-PCR), we used SNP-arrays to identify and map the 11p15 duplications. We report 19 new patients with SRS (n=9) and BWS (n=10) carrying de novo or familial 11p15 duplications, which completely or partially span either both telomeric and centromeric domains or only one domain. Results: Large duplications involving one complete domain or both domains are associated with either SRS or BWS, depending on the parental origin of the duplication. Genotype-phenotype correlation studies of partial duplications within the telomeric domain demonstrate the prominent role of IGF2, rather than H19, in the control of growth. Furthermore, it highlights the role of CDKN1C within the centromeric domain and suggests that the expected overexpression of KCNQ1OT1 from the paternal allele (in partial paternal duplications, excluding CDKN1C ) does not affect the expression of CDKN1C . Conclusions: The phenotype associated with 11p15 duplications depends on the size, genetic content, parental inheritance and imprinting status. Identification of these rare duplications is crucial for genetic counselling.